Genetic susceptibility for autoimmune diseases and white blood cell count - Nataraja Sarma Vaitinadin; C. Michael Stein; Jonathan D. Mosley; Vivian K. Kawai (Scientific Reports, 2023)
Abstract Some autoimmune (AI) conditions affect white blood cell (WBC) counts. Whether a genetic predisposition to AI disease associates with WBC counts in populations expected to have low numbers of AI cases is not known. We developed genetic instruments for 7 AI diseases using genome-wide association study summary statistics. Two-sample inverse variance weighted regression (IVWR) was used to determine associations between each instrument and WBC counts. Effect size represents change in transformed WBC counts per change in log odds-ratio of the disease. For AI diseases with significant associations by IVWR, polygenic risk scores (PRS) were used to test for associations with measured WBC counts in individuals of European ancestry in a community-based (ARIC, n = 8926), and a medical-center derived cohort (BioVU, n = 40,461). The IVWR analyses revealed significant associations between 3 AI diseases and WBC counts: systemic lupus erythematous (Beta = − 0.05 [95% CI, − 0.06, − 0.03]), multiple sclerosis (Beta =  − 0.06 [− 0.10, − 0.03]), and rheumatoid arthritis (Beta = 0.02 [0.01, 0.03]). PRS for these diseases showed associations with measured WBC counts in ARIC and BioVU. Effect sizes tended to be larger among females, consistent with the known higher prevalence of these diseases among this group. This study shows that genetic predisposition to systemic lupus erythematosus, rheumatoid arthritis, and multiple sclerosis was associated with WBC counts, even in populations expected to have very low numbers of disease cases.